2013
DOI: 10.1109/tcpmt.2013.2243203
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anisotropic Conductive Films Based on Vertical Fibers for Post-CMOS Wafer-Level Packaging

Abstract: Abstract-In this paper, we investigate the mechanical and electrical properties of an anisotropic conductive film (ACF) on the basis of high-density vertical fibers for a wafer-level packaging (WLP) application. As part of the WaferBoard, a reconfigurable circuit platform for rapid system prototyping, ACF is used as an intermediate film providing compliant and vertical electrical connection between chip contacts and a top surface of an active wafer-size large-area IC. The chosen ACF is first tested by an inden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…It is concluded that the contact resistances can be the major contributing factor in this bonding system. A comparable finding is reported in [31] with the ACF based on vertical fibers where the contact resistance of such ACF under a compression interconnect system is the major contributor in the total resistance. However, the possible causes for the contact resistance in this paper may be different.…”
Section: A Bonding Influence On Z-axis Resistancesupporting
confidence: 87%
“…It is concluded that the contact resistances can be the major contributing factor in this bonding system. A comparable finding is reported in [31] with the ACF based on vertical fibers where the contact resistance of such ACF under a compression interconnect system is the major contributor in the total resistance. However, the possible causes for the contact resistance in this paper may be different.…”
Section: A Bonding Influence On Z-axis Resistancesupporting
confidence: 87%
“…Conductive fibers have also been used instead of particles for ACFs. (31) Herein, the configuration of the electrode is the same as that of BPE films in ECL imaging. Therefore, we assume that commercially available ACFs can be used as BPE films for ECL imaging.…”
Section: Introductionmentioning
confidence: 99%